Interpretation of geodetic observations of the high-rise buildings displacements - Schults, Roman; Annenkov, Andriy; Bilous, Mykola; Kovtun, Valentyn (Geodesy and Cartography, 2016)
In the article presents a new approach to processing results of geodetic observations of the highrise buildings displacements. As a result of three cycles of observations of the spatial position of deformation marks on the facade of high-rise buildings have been obtained displacements, the nature of which does not allow to correctly determine the nature of the deformation of the building. The obtained values of displacements may correspond to the roll, the bend or twist of the building, as well as combinations of these types of deformations. In this paper, we propose a method for analyzing displacements of a high-rise building with the approximation of the results of observations by spatial curves. The equations of a line, parabolic curve, helix and conical helix were investigated. The technique of construction of displacements approximation models was gave. The approach evaluating the quality of construction of the proposed models was considered. The results showed the effectiveness of the proposed methodic. On the example of results processing of the experimental observations performed construction of displacements models. The optimal solution is obtained using a helix equation. This equation can be used for calculating the twist and bend of structures and for predicting future displacements.